ANALISIS HADIS RIWAYAT BUKHORI NOMOR 4700 SYARAT CALON ISTERI - Siregar, Dame (IAIN Padangsidimpuan, 2019)
Marriage requirements must be fulfilled before holding the qobul marriage contract. The law of dowry is fardu and the sunnah. Mahar is given by the husband to the wife after the first wati, if the same is the acknowledgment before the marriage contract that he is an officer. If it is not official then it must be divorced, because unlawful marriage one of them has committed adultery willingly. Mahar agreed before and after the marriage contract. Mahar must be paid by the husband half if divorced before the first wati, but may be forgiven by his ex-wife or guardian, if before the marriage ceremony the dowry has been determined together and and there is no iddah, if there is regret the ex-husband wants to marry her from the beginning of the marriage, dowry, consent qobul. If the dowry has not been determined yet, but the husband is the wife of the wife before the inheritance, then the husband gives gifts to the wife according to the ability of the ex-husband, and there is no doubt, if there is regret the ex-husband wants to marry her from the beginning of the dowry, qobul. Terms of Islamic wives or husbands, balig, if you haven't delayed the wati according to balig. If you still want a woman to be a silence, if the widow has to say yes or want and other terms. The permission of the prospective wife's guardian must be well known, not to be engineered and other fraudulent methods, whether for officers or widows. Prospective husbands or wives should be knowledgeable, gifted, good descendants, and have religion (know mmebca Al-Qur’an, hadith, Mengethui aratinya, fardu 'ain and kifayah, peraktek worship, know which ones are haram and halal, not just like Muslim in identity card. converts must first study the teachings of Islam well. If the adherent is obliged to wait for the marriage one year from the beginning of adultery, then the adulterer and adulterer may be married after a year is awaited. If there is a child resulting from a woman's adultery, then becoming a child is not father's child, guardian of marriage later when married the child is a marriage guardian.Prospective of husband or wife do not be adulterer, LGBT, drinkers of khomar, smokers, thieves, murderers, fraudsters.Do not gather or polygamy between two sisters, with sisters or siblings or a thousand, or with a bundle of wives, either in the same age or as a whole or as a whole, ethics from either a mother or a mother or a mother. although not yet born by biological children. Do not the woman in which her biological mother has been entrusted, if not married, may be allowed to marry. Do not wife other people either Muslim or non-Muslim who are still legitimate. Do not the woman in the other boy's proposal, as well as the woman still iddah whether he is dead, crai or the woman who is married to her husband. Don't muharromah women based on the Koran and Hadith